PW 2321 Human responses to five heated hypothermia enclosure systems in a cold environment. (November 2018) - Dutta, Ramesh; Kulkarni, Kartik; Gardiner, Phillip; Steinman, Alan; Giesbrecht, Gordon
Abstract : Objective: The purpose of the study was to determine, and compare, the effectiveness of five heated hypothermia enclosure systems (HES). Methods: This study compared the thermal, physiologic and subjective responses of five subjects (one female) in five HES (with vapor barrier and chemical heat sources) during 60 min of exposure to a −22°C climate. The five systems were: 1) user-assembled (Control); 2) Doctor Down® Rescue Wrap® (DD); 3) Hypothermia Prevention and Management Kit (HPMK®); 4) MARSARS Hypothermia Stabilizer Bag (M); and 5) Wiggy's Victims Casualty Hypothermia Bag (W). Core temperature, skin heat loss, and metabolic heat production were determined continuously. Subjective responses were also evaluated for: whole body cold discomfort; overall shivering rating; temperature rating; and overall preferential ranking. Results: Total heat loss was higher with HPMK, W and M compared to Control and DD (p<0.05). Net heat gain was higher with the Control and DD compared to W and M (p<0.05). Control, M and DD consistently scored better in the subjective scales. Conclusions: Although all systems provide insulation and heat, the Control (user-assembled), MASARS and Doctor Down systems were more effective, and preferred. Funding: NSERC, Canada.